FEASIBILITY AND ACCEPTABILITY OF MHEALTH TECHNOLOGIES FOR BEHAVIORAL TRACKING AMONG OLDER ADULTS WITH ARTHRITIS. (11th November 2018) - Zaslavsky, O; Thompson, H; Landis, C; McCurry, S; Ward, T; Heitkemper, M; Demiris, G
Abstract: Background: It is not known if wearable activity trackers (e.g., Fitbit) are feasible and acceptable for use among older individuals with arthritis. Our objective was to assess the feasibility of using a wearable device and related app for activity tracking. We examined (1) frequency of accessing the app over time; (2) average wear time; and (3) if participants judged the technology satisfying, intuitive and free of major technological challenges. Methods: We provided wearable devices and installed a proprietary app on smartphones of participants enrolled in a physical activity and sleep study delivered from June 2017 to March 2018. Direct mailing was used to recruit participants 65 years and older with diagnosed arthritis from a health care organization in Seattle. Participants also needed to meet the following additional criteria: 1) able to walk, yet generally sedentary, 2) endorsed sleep disturbance and 3) own smartphone. Results: We screened 46 and recruited 23 participants ranging in age from 66 to 80 years (mean 71), most were women (70%). Participants who completed the study as of March 15th, 2018 (n=7) wore the device for a mean of 1318 min per day over 4 months and demonstrated almost daily access to the app. In follow up interviews they also reported high satisfaction, stating the technology was easy to use, motivating and useful for self-tracking. Conclusion: Findings demonstrate that it is feasible to recruit and retain older participants with arthritis for research with wearable mHealth technologies and that they find this technology acceptable.